Tick Saliva and the Alpha-Gal Syndrome: Finding a Needle in a Haystack - Sharma, Surendra Raj; Karim, Shahid (Frontiers in Cellular and Infection Microbiology, 2021)
Ticks and tick-borne diseases are significant public health concerns. The presence of bioactive molecules in tick saliva facilitates prolonged blood feeding and transmission of tick-borne pathogens to the vertebrate host. Alpha-gal syndrome (AGS), a newly reported food allergy, is induced by saliva proteins decorated with a sugar molecule, the oligosaccharide galactose-⍺-1,3-galactose (α-gal). This syndrome is characterized by an IgE antibody-directed hypersensitivity against α-gal. The α-gal antigen was discovered in the salivary glands and saliva of the Lone Star tick (Amblyomma americanum). The underlying immune mechanisms linking tick bites with α-gal-specific IgE production are poorly understood and are crucial to identifying novel treatments for this disease. This article reviews the current understanding of AGS and its involvement with tick species.